Acceptance of smallholders in oil palm industry toward integrated farming system / Mohd Tahir Bahari - Bahari, Mohd Tahir (Faculty of Plantation and Agrotechnology, 2016)
Malaysian agriculture is specified by mixed farming practices which form the backbone of farming systems. Integrated farming system is an incorporate crop commodities (livestock) and primary crop (oil palm). The purpose of this study was to identify the factors of an acceptance of smallholder towards integrated farming and to examine the most influenced factor for acceptance of smallholder towards integrated farming in several areas in Bera, Pahang. Researchers get a sample of 155 respondents, and examine whether factors such as the increase in crop yields, increase profits, increase productivity, improve soil fertility, reduce cost, reduce risk and environmentally friendly are the factors that contribute to the acceptance for this topic. The study was conducted using questionnaires that were distributed to the respondents and the results analyzed using reliability test and Pearson correlation analysis using the Statistical Package for Social Sciences (SPSS). From the analysis, the researchers found that all of the factors have strong and significant relationships and only two factors which are increase profit and reduce risk influenced the acceptance of smallholder towards integrated farming in palm oil industry. Other factors have relationship with acceptance smallholders but not influenced them because most of the smallholders have lack in knowledge about integrated farming system. These become responsible by government agencies and others to help the smallholders in term of access information of integrated farming systems and its future positive impact, give guideline advertising, awareness campaign and offering package of incentives in available to promote the systems.